Trends in private investment in developing countries. No.41, Statistics for 1970-1998 - Bouton, Lawrence (The World Bank, 2000)
This discussion paper examines in its first part, the role of private investment in economic growth. While theoretical growth models developed in the economics literature, make no distinction between private, and public components of investment, there is an emerging appreciation that private investment is more efficient, and productive tan public investment. Results from the recent empirical literature, updated here with the recent data on private investment, suggest that private investment has a stronger association with long run economic growth than public investment. The second part shows trends in private, and public fixed investment in fifty developing countries. On average, the ratio of private investment to GDP continued its upward trend, reaching record levels in 1998, the most recent year for which comparable data exist. That year, average private investment reached 14.3 percent of GDP, but public investment, fell to only 7.0 percent of GDP, its lowest level since 1974